Synthesis and biological evaluation of palmyrolide A macrocycles as sodium channel blockers towards neuroprotection. Issue 36 (18th August 2016) - Philkhana, Satish Chandra; Mehrotra, Suneet; Murray, Thomas F.; Reddy, D. Srinivasa
Abstract : A detailed account on total synthesis, analogue synthesis, biological evaluation and SAR of palmyrolide A macrocycles towards sodium channel inhibition is reported. Abstract : Palmyrolide A is a neuroprotective macrolide isolated by Gerwick and coworkers in 2010. This natural product is known to suppress neuronal spontaneous calcium ion oscillations through its voltage-gated sodium channel blocking ability which is of significant interest in CNS drug discovery. Herein, we give a detailed account on total synthesis of (+)-palmyrolide A and synthesis of a focused library of macrocycles around the scaffold, followed by their biological evaluation. Use of the chiral pool approach, Zhu's oxidative homologation, access to unnatural cis -palmyrolide A, preparation of 18 new analogues and identification of macrolides with improved sodium channel blocking activity are the important features of the present paper. As a measure of potency as voltage-gated sodium channel blockers, all the synthesized analogues were profiled for their ability to inhibit the veratridine-stimulated Na + influx in murine primary neuronal cultures. Four macrocycles were found to be more potent or comparable to that of the natural product (−)-palmyrolide A. The most potent compound from this series20 was structurally simplified and readily accessible in good quantities for further biological profiling.